Abnormal Development of Dendrites in Adult-Born Rat Hippocampal Granule Cells Induced by Cyclophosphamide - Wu, Lin; Guo, Dandan; Liu, Qi; Gao, Fei; Wang, Xiaochen; Song, Xueying; Wang, Fuwu; Zhan, Ren-Zhi (Frontiers in Cellular Neuroscience, 2017)
Although development of cognitive decline in cancer patients who receive chemotherapy is common, the underlying mechanism(s) remains to be identified. As abnormalities in adult hippocampal neurogenesis may serve as substrate for cognitive dysfunction, the present study examines the effect of cyclophosphamide (CPP), a widely prescribed chemotherapeutic agent, on dendritic development of adult-born hippocampal granule cells in the rat. CPP was intraperitoneally injected into male Sprague-Dawley rats once a week for four consecutive weeks. Four weeks and one week after the last dose of CPP, Morris water maze test and doublecortin immunohistochemistry were carried out to determine the effects of CPP on cognitive function and the rate of hippocampal neurogenesis, respectively. Adult newborn hippocampal granule cells were labeled at the same day as the first dose of CPP and were examined 10 weeks after labeling. Results showed that cognitive decline induced by CPP was associated with both suppressed adult hippocampal neurogenesis and abnormal development of dendrites of newborn granule cells. The abnormalities of dendrites in newborn granule cells after CPP exposure included less dendritic branching, shorter total dendritic length, thinner and torturous dendritic shafts with intermittent appearances of varicosities, and lower spine densities of stubby and thin types along dendritic shafts, but an increased density of mushroom-like spines. Adult-born granule cells in the presence of cyclophosphamide, a widely used anti-cancer medication, display abnormal dendritic morphologies and fewer dendritic spines which may underlie cognitive dysfunction.